Kinase Partner Protein Plays a Key Role in Controlling the Speed and Shape of Pollen Tube Growth in Tomato . Issue 4 (5th October 2020) - Liu, Hai-Kuan; Li, Yu-Jie; Wang, Shu-Jie; Yuan, Ting-Lu; Huang, Wei-Jie; Dong, Xin; Pei, Jia-Qi; Zhang, Dong; McCormick, Sheila; Tang, Wei-Hua
Abstract : A tomato kinase partner protein links actin cytoskeleton regulators to pollen receptor kinase signaling and Rho-of-Plants GTPase activation, thereby modulating pollen tube growth. Abstract: The rapid and responsive growth of a pollen tube requires delicate coordination of membrane receptor signaling, Rho-of-Plants (ROP) GTPase activity switching, and actin cytoskeleton assembly. The tomato ( Solanum lycopersicum ) kinase partner protein (KPP), is a ROP guanine nucleotide exchange factor (GEF) that activates ROP GTPases and interacts with the tomato pollen receptor kinases LePRK1 and LePRK2. It remains unclear how KPP relays signals from plasma membrane-localized LePRKs to ROP switches and other cellular machineries to modulate pollen tube growth. Here, we biochemically verified KPP's activity on ROP4 and showed that KPP RNA interference transgenic pollen tubes grew slower while KPP -overexpressing pollen tubes grew faster, suggesting that KPP functions as a rheostat for speed control in LePRK2-mediated pollen tube growth. The N terminus of KPP is required for self-inhibition of its ROPGEF activity, and expression of truncated KPP lacking the N terminus caused pollen tube tip enlargement. The C-terminus of KPP is required for its interaction with LePRK1 and LePRK2, and the expression of a truncated KPP lacking the C-terminus triggered pollen tube bifurcation. Furthermore, coexpression assays showed that self-associated KPP recruited actin-nucleating Actin-Related Protein2/3 (ARP2/3) complexes to the tip membrane. Interfering with ARP2/3 activity reduced the pollen tube abnormalities caused by overexpressing KPP fragments. In conclusion, KPP plays a key role in pollen tube speed and shape control by recruiting the branched actin nucleator ARP2/3 complex and an actin bundler to the membrane-localized receptors LePRK1 and LePRK2.